Tenecteplase in acute ischemic stroke: a new era in thrombolysis - Silva, Gisele Sampaio; Rocha, Eva; Pontes-Neto, Octávio Marques; Martins, Sheila Ouriques (Arquivos de Neuro-Psiquiatria, 2025)
Tenecteplase (TNK) is a genetically engineered variant of alteplase, showing promise for acute ischemic stroke treatment. With a longer half-life and higher fibrin specificity, TNK enables more targeted and efficient clot dissolution. Clinical trials demonstrate potential advantages, including improved reperfusion rates and functional outcomes with lower systemic bleeding. Though not officially approved for this purpose by all regulatory agencies, TNK is used off-label and in acute stroke guidelines due to its ease of administration and effectiveness. The 0.25 mg/kg dosage within 4.5 hours of symptom onset was shown to be consistently effective and safe. Further trials are expected to identify patient subgroups that benefit most from TNK treatment. The present narrative review assesses the existing literature and evidence regarding the use of tenecteplase for the treatment of acute ischemic stroke.
Keywords: Ischemic Stroke; Thrombolytic Therapy; Tenecteplase